Synthesis of RBa₂Cu₃O₇₋₈ (R=Gd, Ho, Sm) Ceramic Superconductor Via Coprecipitation Method and Effects of Heat Treatment - Ahmad Rusli, Ahmad Mustaza (2010)
Preparation of R-123 using conventional solid state method requires high purity oxides and carbonate powders as starting materials, multiple grindings and extended heat treatment to achieve a complete reaction via solid state diffusion. However, high sintering temperature (> 940 °C) and long heating duration (48 - 100 hours) would cause the composition of compound to change, and consequently lowers the quality of the samples. Co-precipitation method (COP) has the capability to overcome these problems because the initial mixtures of cations in the solution are in atomic scale. This enhances the reaction during the heat treatment and the resulting starting powders are more homogenous with grain size in the nanometer range, higher purity than the powders produced by the solid state method at shorter thermal and processing time. COP method was used to prepare nanosize metal oxalate (> 50 nm) of R-123 superconductors and the oxalate powders were analyzed via Thermogravimetric Analysis (TGA). Five major drops due to the loss of weight from the bulk sample in the formation of R-123 were observed. Base on the TGA results and previous studies, the calcinations was carried out at 900 – 960 °C. The calcined samples were pelletized and sintered under oxygen atmosphere for 15 hours at 920 ºC, 930 ºC, 940 ºC and 950 ºC. Larger grains (~ 20 μm) which were highly compacted and randomly distributed were observed for the resulting sintered samples by Scanning Electron Microscopy (SEM). The Ho-123 and Sm-123 samples which were preheated and calcined at 900 ºC, followed by sintering at 920 ºC gave single-phased compounds as confirmed by the X-Ray Diffraction (XRD). However, secondary phase of R-211 can be observed for Gd-123 samples that were treated with the same heat treatment. In resistivity measurement critical current, IC and transition temperature, TC for R-123 samples were observed above 200 mA and 90 K. However, Sm-123 showed decreasing IC when the sintering temperature was increased and zero transition temperature, TC(R=0) for Sm-123 and Ho-123 sintered at 950 ºC were below 90 K.